2018
DOI: 10.1002/14651858.cd009676.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for symptomatic gastroparesis

Abstract: Analysis 2.4. Comparison 2 Acupuncture versus gastrokinetic agents, Outcome 4 Proportion of people whose symptoms 'improved' (long-term: more than 12 weeks) (acupuncture versus mosapride). . . . . . . . . . . . . Analysis 2.5. Comparison 2 Acupuncture versus gastrokinetic agents, Outcome 5 Changes in the rate of gastric emptyingresponse rate (acupuncture versus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…There is borderline support (78% agreement) for the use of prokinetics as a group, but the panel agreed on the use of 5‐HT 4 receptor agonists as a class 76–89 . There is also no consensus on the use of other neuromodulators, herbal therapies, acupuncture or psychological therapies in gastroparesis 90–93,116–118 . The same is true for invasive therapies such as botulinum toxin injection, GES, pyloric endoscopic myotomy or (partial) gastrectomy 95–113 .…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is borderline support (78% agreement) for the use of prokinetics as a group, but the panel agreed on the use of 5‐HT 4 receptor agonists as a class 76–89 . There is also no consensus on the use of other neuromodulators, herbal therapies, acupuncture or psychological therapies in gastroparesis 90–93,116–118 . The same is true for invasive therapies such as botulinum toxin injection, GES, pyloric endoscopic myotomy or (partial) gastrectomy 95–113 .…”
Section: Recommendationsmentioning
confidence: 99%
“…A Cochrane systematic review found overall higher symptom improvement rates with acupuncture compared to usual or medical therapy, but due to the heterogeneity and low quality of studies, and the risk of bias, the conclusion is considered uncertain. 118 Several algorithms propose nutritional support in the form of enteral or parenteral nutrition for refractory gastroparesis with weight loss and/or nutritional deficiencies. 44,71,119 While short-term parenteral nutrition may provide rapid weight recovery, its longterm use should be avoided for risk of catheter-related sepsis and hepatotoxicity.…”
mentioning
confidence: 99%
“…Gastroparesis is characterized by delayed gastric emptying with associated upper abdominal symptoms and is often a complication of diabetes-induced hyperglycemia or surgery ( 56 ). A systematic review of acupuncture for the treatment of gastroparesis found preliminary qualitative evidence that acupuncture provided short-term improvement in symptoms of gastroparesis, regardless of etiology (i.e., diabetes, surgery) ( 57 ). These findings point to the use of acupuncture to mitigate abdominal pain related to gastroparesis; however, the findings were characterized as low-certainty or very-low certainty evidence and should be interpreted with caution.…”
Section: Evidence Acquisitionmentioning
confidence: 99%
“…25 A systematic review demonstrated that acupuncture is a low-risk treatment that may have short-term benefits for patients with gastroparesis and we can conclude that there is a low level of evidence to fully support this as a mainstay of treatment at this time. 26 Patients with refractory gastroparesis (failed nutritional/ psychological therapy, failure of medication therapy, recurrent hospitalization, nutritional deficiency) should be considered for interventional therapy (endoscopic vs. surgical). These can be further divided into therapies specifically targeting the pylorus as opposed to a more generalized gastric approach.…”
Section: Treatment Optionsmentioning
confidence: 99%